Concordat and the Rights of Minority Religious Associations in Poland - Łabieniec, Paulina (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The article aims to show the impact of the concordat between the Republic of Poland and the Holy See from 1993 on the legal situation of other religious associations in Poland. Representatives of churches affiliated with the Polish Ecumenical Council expressed concerns that certain rights granted to the Catholic Church in the concordat would violate the autonomy of minority churches. As a result of the debate over the concordat, the Polish Ecumenical Council formulated a number of postulates for expanding the rights of other religious associations, such as the right to conclude marriages in churches with effects in civil law. Many of the postulates were established in individual laws passed in 1994–1997 regulating the state’s relations with churches and other religious associations. A guarantee of bilateral arrangement of relations between the state and religious associations – on the model of the Concordat – was to be Article 25(5) of the new 1997 Constitution, stipulating that relations between the Republic of Poland and other churches and religious associations shall be determined by laws passed on the basis of agreements concluded by the Council of Ministers with their competent representatives. However, this provision remains unused, as evidenced by the failure to conclude any agreement and pass an individual law comprehensively regulating the legal situation of religious associations in Poland after the Constitution came into force, despite the expression of such a will by thirty churches and other religious associations. The Concordat has contributed to expanding the rights of other religious associations in Poland but in the absence of the application of Article 25(5) of the Constitution, it remains the act that best guarantees bilateral arrangement of relations between the state and religious association.